(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
The objective was to describe and evaluate a model of drug dispensing developed and implemented in a community pharmacy in Brazil. This was a descriptive, observational, quasi-experimental study performed in the period between 21 January 2013 and 20 April 2013. The model was evaluated and described in terms of three parameters: structure, process and outcome. The description and assessment of each parameter was performed as follows: (I) Structure: profile of patients, pharmacist's professional profile, physical facility, informational material; (II) Process: drug-related problems, pharmaceutical interventions performed, results of pharmaceutical interventions; (III) Outcome: patient knowledge of medications. Dispensing service improved patient knowledge of medications (p < 0.05), which was associated with pharmacotherapy complexity (p < 0.05). The main problems identified were related to lack of patient knowledge regarding their medication (52.9%). Pharmaceutical interventions were mostly performed directly to the patients (86.3%) by verbal (95.4%) and written (68.2%) information, and most of the problems were completely solved (62.7%). The medicine dispensing model was able to identify and solve drug-related problems and promote an improvement in patient knowledge about medication.